Induced Pluripotent Stem Cells: Development in the Ophthalmologic Field - Nan Wu; Marianne Doorenbos; Dong Feng Chen (Hindawi Limited, 2016)
Human induced pluripotent stem cells (iPSCs) are a type of stem cells that can be derived from human somatic cells by introducing certain transcription factors. Induced pluripotent stem cells can divide indefinitely and are able to differentiate into every cell type, which make them viable for transplantation and individual disease modeling. Recently, various ocular cells, including corneal epithelial-like cells, retinal pigment epithelium (RPE) cells displaying functions similar to native RPE, photoreceptors, and retinal ganglion cells, have all been successfully derived from iPSCs. Transplantation of these cells in animal models showed great promise for reversing blindness, and the first clinical trial on humans started in 2013. Despite these promising results, more research is in demand for preventing inadvertent tumor growth, developing precise functionality of the cells, and promoting integration into the host tissue.